2009
DOI: 10.1111/j.1872-034x.2009.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin prevents progression of steatohepatitis in mice by regulating oxidative stress and Kupffer cell phenotype polarization

Abstract: Lack of adiponectin enhanced, and adiponectin administration prevented steatohepatitis progression in mice. These changes were due to the anti-oxidative effects of adiponectin, and its effects on Kupffer cells recruitment and phenotype polarization. Augmentation of adiponectin effects could be a useful preventive approach for NASH progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
71
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 52 publications
(100 reference statements)
4
71
0
1
Order By: Relevance
“…30 Another study suggested an antioxidant role for adiponectin during liver injury, in addition to its effect on Kupffer cell recruitment. 11 We recognize that the detailed mechanism of action by which adiponectin exerts its potent protective effects on stellate cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Another study suggested an antioxidant role for adiponectin during liver injury, in addition to its effect on Kupffer cell recruitment. 11 We recognize that the detailed mechanism of action by which adiponectin exerts its potent protective effects on stellate cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…4 Adiponectin has been suggested to play an important role in the pathogenesis of liver fibrosis. [7][8][9][10][11][12][13][14][15] Notably, in addition to adipose tissue, adiponectin is expressed in stellate cells. 16 Previous studies have shown that adiponectin has important effects specifically on stellate cells, and the mechanism of these effects remains an area of active investigation.…”
mentioning
confidence: 99%
“…Adiponectin knockout mice also appear to have more hepatic steatosis and activated Kupffer cells than wild-type mice [34,35]. The liver of transgenic mice overexpressing Adipoq is characterised by increased fatty acid oxidation leading to decreased hepatic triacylglycerol content and increased hepatic and systemic insulin sensitivity [17,32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed beneficial effects of adiponectin signalling in many organs including the liver. Specifically, adiponectin signalling alleviated or prevented NASH in mice, 33,34 and associations of hypoadiponectinaemia with fatty liver and/or NASH have been reported in humans. 35,36 Furthermore, genetic studies revealed associations of ADIPOR1/2 with IR and liver fat content, 37,38 and overexpression of ADIPOR1/2 has been shown to potentiate subeffective doses of adiponectin.…”
Section: Discussionmentioning
confidence: 99%